Teachers: We are resistance, our voice needs to be a shout (Revista Contexto & Educação, 2023)
This work aims to present reflections of high school teachers and their pedagogical practices with High School youth from public schools on the outskirts; practices, these, considered as resistance in the current educational political context. We sought, therefore, to investigate the processes of resistance used by teachers of this school, from a field research developed through the methodological assumptions of sociopoetics with a group of 14 teachers from different areas of knowledge, their reflexion are of manifest contribution for the comprehension of how much we will have, go and resist. We conclude that the Education for those who have few financial conditions or is not part of a “chosen group” to “be someone in life”, is the bigger act of insurrection that a poor young can do and that this rebellion act is the struggle manifestation and the teachers resistance who have their solid feet on the ground that the school represents and that believe in the power of opportunity and a released possibility that only the education is capable to reach.
Keywords: Teachers. High School. Pedagogical practice. Knowledge construction. Sociopoetics.